Spectrum of thyroid disorders among patients with type 2 diabetes mellitus - Md Rakibul Hasan; Raisa Siddika; Sayma Akther Mou; Md Shahed Morshed (IMC Journal of Medical Science)
Background and objectives: Thyroid disorders (TD) are common among patients with type 2 diabetes mellitus (T2DM). Information on types of functional and structural TDs among Bangladeshi patients with T2DM is scarce in the literature. The present study aimed to determine the magnitude and characteristics of different TDs among Bangladeshi diabetic patients attending an urban healthcare center in Dhaka.